Nanostructured carbon electrocatalysts for clean energy conversion and storage: A mini review on the structural impact - Yang, Mengqing; Wang, Mengjie; Zhang, Minna; Sun, Xun; Xuan, Xiaoxu (Frontiers in Materials, 2022)
Electrochemical conversions of carbon dioxide, water, oxygen, and nitrogen have offered effective ways to relieve the problems of carbon dioxide over-emission and fluctuated energy (such as solar, wind, tide, etc.) storage. The key factor that impacts the electrochemical system’s performance is the catalysts employed. Among all the materials, carbon nanomaterials generally exhibit high catalytic activity which is attributed to the high conductivity, large specific surface area, and exposed active sites. Recently, more and more researchers set their sights on applying the carbon nanomaterials in large-scale projects. Herein, it is of great importance to review the most recent studies on carbon nanomaterials in electrochemical applications. This paper summarizes the applications of carbon nanomaterials in electrochemical applications, and the structure impact on the performance. Further, challenges in this field are discussed, which can guide the innovative synthesis of efficient nanostructured carbon electrocatalysts for practical, large-scale energy conversion applications.